Association Between Pain and Frailty in Middle-Aged and Older Patients: The Mediating Roles of Sleep and Mood - Wang HP; Wang T; Ye HT; Dong YY; Zhao SJ; Liu QR; Hu XY; Ji MH; Yang JJ (Clinical Interventions in Aging, 2025)
Hua-Peng Wang,1,* Tao Wang,1,* Hao-Tian Ye,1 Yong-Yan Dong,1 Shi-Jie Zhao,1 Qing-Ren Liu,2 Xiao-Yi Hu,3 Mu-Huo Ji,3 Jian-Jun Yang1 1Department of Anesthesiology, Pain and Perioperative Medicine, The First Affiliated Hospital of Zhengzhou University, Zhengzhou, Henan, People’s Republic of China; 2Department of Anesthesiology, Xishan People’s Hospital of Wuxi City, Wuxi, Jiangsu, People’s Republic of China; 3Department of Anesthesiology, The Second Affiliated Hospital of Nanjing Medical University, Nanjing, Jiangsu, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jian-Jun Yang, Department of Anesthesiology, Pain and Perioperative Medicine, The First Affiliated Hospital of Zhengzhou University, No. 1, Longhu Zhonghuan Road, Jinshui District, Zhengzhou, Henan Province, 450018, People’s Republic of China, Email yjyangjj@126.com Mu-Huo Ji, Department of Anesthesiology, The Second Affiliated Hospital of Nanjing Medical University, No. 262, North Zhongshan Road, Gulou District, Nanjing, Jiangsu Province, 210003, People’s Republic of China, Email jimuhuo2009@sina.comPurpose: Pain and frailty are significantly social concerns negatively affecting physical and mental health in middle-aged and older population. This study aimed to investigate the association between pain and frailty, with a particular focus on the mediating roles of sleep and mood.Patients and Methods: A cross-sectional study was conducted involving 244 middle-aged and older participants in local hospital. Their pain, frailty, sleep and mental health conditions were assessed through face-to-face interviews. Linear regression analysis was used to examine the association between pain and frailty. Simple and serial mediation models were employed to investigate the complex mediation effects of sleep and mood on pain and frailty.Results: Significant effects were observed in both the pain-frailty nexus and the frailty-pain nexus. For simple mediation models, we identified significant mediation effects of sleep (=0.049, 95% CI: 0.011, 0.094), anxiety (=0.054, 95% CI: 0.023, 0.094), and depression (=0.093, 95% CI: 0.049, 0.150) in the pain-frailty nexus. Similarly, in the frailty-pain nexus, sleep (=0.096, 95% CI: 0.043, 0.162), anxiety (=0.085, 95% CI: 0.029, 0.156), and depression (=0.126, 95% CI: 0.056, 0.208) continued to be significant mediators, while sleep and depression had more significant mediating effects than anxiety. Serial mediation models revealed that sleep and depression jointly played a sequential mediation role in the frailty-pain nexus (=0.020, 95% CI: 0.002, 0.044; =0.043, 95% CI: 0.014, 0.081).Conclusion: Our research provided evidence supporting the robust association between pain and frailty and offered new sights into potential strategies by enhancing sleep quality and mental health for preventing and managing both pain and frailty.Keywords: pain, frailty, sleep, mood, middle-aged and older adults